The importance of context and cognitive agency in developing police knowledge: Going beyond the police science discourse. (June 2018) - Wood, Dominic; Cockcroft, Tom; Tong, Stephen; Bryant, Robin
This paper argues the current exposition of police knowledge through the discourses of police science and evidence-based policing (EBP) leads to exaggerated claims about what is, and can be, known in policing. This new orthodoxy underestimates the challenges of applying knowledge within culturally mediated police practice. The paper draws upon virtue epistemology, highlighting the role that cognitive agency plays in establishing knowledge claims. We challenge the assumption that it is possible to derive what works in all instances of certain aspects of policing and suggest that it would be more apt to speak about what worked within a specific police context.